Grammar and vocabulary for first and first for schools - Thomas, Barbara (Cambridge University Press, 2015)
Grammar and Vocabulary reference and practice for the revised Cambridge English: First (FCE) and Cambridge English: First (FCE) for Schools from 2015 Cambridge Grammar and Vocabulary for First and First for Schools provides complete coverage of the grammar and vocabulary needed for the Cambridge First exams, and develops listening skills at the same time. It includes the full range of First and First for Schools exam tasks from the Reading and Use of English, Writing and Listening papers, and contains helpful grammar explanations. This edition is updated for the new exam to be introduced from 2015. It is informed by the Cambridge Learner Corpus to ensure that the language tackles real learner errors. The accompanying listening material is available online for download